Concordant phylogeographic responses to large‐scale coastal disturbance in intertidal macroalgae and their epibiota. Issue 2 (5th November 2021) - Parvizi, Elahe; Dutoit, Ludovic; Fraser, Ceridwen I.; Craw, Dave; Waters, Jonathan M.
Abstract: Major ecological disturbance events can provide opportunities to assess multispecies responses to upheaval. In particular, catastrophic disturbances that regionally extirpate habitat‐forming species can potentially influence the genetic diversity of large numbers of codistributed taxa. However, due to the rarity of such disturbance events over ecological timeframes, the genetic dynamics of multispecies recolonization processes have remained little understood. Here, we use single nucleotide polymorphism (SNP) data from multiple coastal species to track the dynamics of cocolonization events in response to ancient earthquake disturbance in southern New Zealand. Specifically, we use a comparative phylogeographic approach to understand the extent to which epifauna (with varying ecological associations with their macroalgal hosts) share comparable spatial and temporal recolonization patterns. Our study reveals concordant disturbance‐related phylogeographic breaks in two intertidal macroalgal species along with two associated epibiotic species (a chiton and an isopod). By contrast, two codistributed species, one of which is an epibiotic amphipod and the other a subtidal macroalga, show few, if any, genetic effects of palaeoseismic coastal uplift. Phylogeographic model selection reveals similar post‐uplift recolonization routes for the epibiotic chiton and isopod and their macroalgal hosts. Additionally, codemographic analyses support synchronous population expansions of these four phylogeographically similar taxa. Our findings indicate that coastal paleoseismic activity has driven concordant impacts on multiple codistributed species, with concerted recolonization events probably facilitated by macroalgal rafting. These results highlight that high‐resolution comparative genomic data can help reconstruct concerted multispecies responses to recent ecological disturbance.